An Overview of the Eurasian Economic Union and its relationship with Serbia - Haitas, Daniel (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In addition to the European Union, other regional integration projects have arisen in different parts of the world. One prominent example of this is the Eurasian Economic Union (EAEU), which seeks to reintegrate the former Soviet space. It includes among its members Armenia, Belarus, Kazakhstan, Kyrgyzstan, and Russia. To a certain extent the EAEU draws inspiration from the European Union, seeing it as model it can emulate and from which it can learn, where appropriate. The EAEU is open to new members and also seeks partners, including in Europe. An example of this is Serbia, which has expressed interest in signing a free trade agreement with EAEU. From a legal point of view, this is possible, as it is not prohibited by Serbia’s SAA. However, such a development may also have its problematic aspects, which includes Serbia’s obligations if it becomes a fully fledged member of the European Union and the nature of the Common Commercial Policy (CCP).